Silver(I) complexes with quinazoline and phthalazine: synthesis, structural characterization and evaluation of biological activities - Savić, Nada; Glišić, Biljana Đ; Wadepohl, Hubert; Pavic, Aleksandar; Senerovic, Lidija; Nikodinovic-Runic, Jasmina; Djuran, Miloš I. (MedChemComm, 2016)
New silver(I) complexes with quinazoline (qz) and phthalazine (phtz), [Ag(NO3)(qz)]n (1) and {[Ag(CH3CN)]2(μ-phtz)2}[BF4]2 (2), have been synthesized and structurally characterized by using different spectroscopic and single-crystal X-ray diffraction techniques. The obtained results revealed that the reaction of AgNO3 with qz at room temperature in a 2 : 1 molar ratio led to the formation of the polynuclear complex 1. However, the reaction of AgBF4 with phtz under the same experimental conditions resulted in the formation of the dinuclear complex 2. The solution behaviour and air/light stability of these silver(I) complexes have been investigated. The complexes 1 and 2, along with the silver(I) salts used for their synthesis, were evaluated by in vitro antimicrobial studies against a panel of microbial strains that lead to many skin and soft tissue, respiratory, wound, and nosocomial infections. The obtained results indicate that all tested silver(I) compounds have good antibacterial activity with MIC values in the range from 1.5 to 15.6 μg mL−1 against the investigated strains. On the other hand, their antifungal activity against Candida albicans was moderate. In order to determine the therapeutic potential of 1 and 2, their antiproliferative effect on the normal human lung fibroblast cell line MRC5, hemolytic effect on red blood cells and embryotoxicity on zebrafish (Danio rerio) have also been evaluated.
First published 25 Nov 2015
Gesehen am 12.05.2020